Das Scheitern der Kommunikation als Ursprung einer Tragödie – Beobachtungen zur Inkompatibilität von „männlicher“und „weiblicher“ Rationalität in Max Frischs Roman Homo faber - Springer, Bernd F.W. (Revista de Filología Alemana, 2007)
The subject of Max Frisch’s novels Stiller and Homo Faber is the difficult relationship between the genders. In Homo faber the reasons can be found in the different forms of rationality of man and woman that lead to problems of communication, which build the origin of the tragic story.